Thoracic radiotherapy as a risk factor for heart ischemia in subjects treated with chest irradiation and chemotherapy and without classic cardiovascular RISK factors. (November 2020) - Vallerio, Paola; Maloberti, Alessandro; Palazzini, Matteo; Occhi, Lucia; Peretti, Alessio; Nava, Stefano; Soriano, Francesco; Musca, Francesco; De Chiara, Benedetta; Belli, Oriana; Moreo, Antonella; Bisceglia, Irma; et al.
Highlights: Radiation Induced Heart Disease represents a late effect of chest irradiation. Chest irradiation represents a strong cardiovascular risk factor. More studies are needed in order to assess which non-invasive screening tests should be used. Abstract: Background and purpose: Radiation Induced Heart Disease (RIHD) represents a late effect of chest irradiation, contributing in increasing mortality rate in oncological patients by affecting pericardium, myocardium, valvs and coronaries. Currently, regarding the risk of Coronary Artery Disease (CAD), a cardiological screening involving exercise stress electrocardiography after 5–10 years from radiotherapy is advised. We sought to determine the rate of ischemia at exercise stress electrocardiography in a population of patients without cardiovascular risk factors who sustained radiotherapy, using a cohort of patients presenting with at least one cardiovascular risk factor as control group. Design and methods: A population of 115 patients who sustained chest irradiation (and associated chemotherapy), presenting without classic cardiovascular risk factors or typical symptoms suggesting CAD, was evaluated with exercise stress electrocardiography. 135 patients with at least one risk factor for cardiovascular disease candidate to stress testing for primary prevention or for atypical symptoms served as control group. Results: The cohort of irradiated patients without classical cardiovascular risk factors is younger (48.7 ± 10.1 vs 60.5 ± 10.8 years, p  < 0.001) and presents a lower percentage of males when compared with the control group. In this latter group 25.9% of subjects has diabetes, 62.9% dyslipidaemia, 67.4% hypertension and 19.2% actively smoke. Despite this important differences regarding classic cardiovascular risk factors, no significant differences were found in the number of positive exercise stress electrocardiography (10.4 vs 5.9%, p  = ns). Conclusions: Chest irradiation represents a strong cardiovascular risk factor. In fact, prevalence of positive ECG-stress test is not different (nor higher and nor lower) in irradiated subjects without cardiovascular risk and not irradiated patients with classic cardiovascular risk.